2020
DOI: 10.1371/journal.pone.0229183
|View full text |Cite
|
Sign up to set email alerts
|

Divorce and adolescent academic achievement: Heterogeneity in the associations by parental education

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…Approximately 80% of children in single-parent households live with their mother. The pattern of heterogeneity remained unchanged, although the divorce penalties turned out to be slightly stronger, especially for children of highly educated mothers, in line with recent evidence by Nilsen et al (2020). Finally, the divorce penalties in the log odds of tertiary education attainment by parental education, estimated through logistic regression models, are fully consistent with the results obtained using LPMs.…”
Section: The Divorce Penalty In Tertiary Education Attainment Across Time and Spacesupporting
confidence: 84%
See 2 more Smart Citations
“…Approximately 80% of children in single-parent households live with their mother. The pattern of heterogeneity remained unchanged, although the divorce penalties turned out to be slightly stronger, especially for children of highly educated mothers, in line with recent evidence by Nilsen et al (2020). Finally, the divorce penalties in the log odds of tertiary education attainment by parental education, estimated through logistic regression models, are fully consistent with the results obtained using LPMs.…”
Section: The Divorce Penalty In Tertiary Education Attainment Across Time and Spacesupporting
confidence: 84%
“…In addition, the evidence that the socioeconomic heterogeneity of the divorce penalty is even stronger when operationalized using mothers' education instead of the dominance principle suggests that mechanisms other than the loss of the nonresident parent's economic resources may be relevant to explaining the higher divorce penalty for children of highly educated parents. As already argued in other studies that found a similar result (Martin 2012;Nilsen et al 2020), a possible underlying mechanism is the 'double burden' suffered by highly educated (single) mothers regarding work pressure and childrearing responsibilities. That is, highly educated mothers who divorce are less able to transfer their educational advantage than their counterparts who have not divorced, because of reduced time to invest in their children.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Very wealthy and high‐income families can send their children to private schools, which increases the chances of university entry (Jerrim et al, 2016). Undesirable changes in home circumstances (e.g., job loss, divorce) can adversely impact student performance (Lehti et al, 2019; Nilsen et al, 2020). Parents influence their children in myriads of ways and most parents monitor their children's education.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study are also reusable after the COVID-19 pandemic, as the pandemic is merely an environmental factor that exacerbates the problem of mental disorders caused by mobile phone use. Mediating factors of family conflict intensified by the pandemic (eg, reduced time of physical exercise or decrease in family income) can also be caused by other incidents in life, including unemployment, divorce [ 44 , 45 ], and sometimes natural disasters [ 46 ].…”
Section: Discussionmentioning
confidence: 99%